Metabonomics analysis of aqueous humor samples from cataract patients with branch retinal vein occlusion: Metabolomics analysis of cataract combined BRVO - Zhang, Xin; Dai, Binbin; Li, Enhui; Zhang, Yiwen; Huang, Qinzhu; Li, Gaochun; Wang, Ledan (Cellular and Molecular Biology, 2024)
Cataract (CAT) has a very high incidence rate among the middle-aged and elderly, with most patients complicated by branch retinal vein occlusion (BRVO), a key cause of blindness. In this study, through metabolomic analysis of aqueous humor samples from CAT patients with BRVO, a total of 319 different metabolites were found, most of which belonged to the categories of carboxylic acids and derivatives, fatty acyls, and organooxygen compounds. The most typical metabolites were 3-methylhistidine and biliverdin, which were up-regulated, as well as the down-regulated beta-glycerophosphoric acid. Tricosanoic acid showed the most significant correlation with CAT+BRVO. According to the Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis, the most commonly related keywords for differentially expressed metabolites were biosynthesis of unsaturated fatty acids and synaptic vesicle cycle. These results can not only help to further understand the pathogenesis of CAT complicated by BRVO in clinical practice, but also provide some new therapeutic research directions.